There was an old lady who swallowed Fly Guy - Arnold, Tedd. (New York : Scholastic, 2007)
After accidentally swallowing her grandson's pet fly, Grandma tries to retrieve it by consuming progressively larger animals.
F
"Cartwheel books."
b
b
Keywords: Flies -- Juvenile fiction; Pets -- Juvenile fiction; Grandmothers -- Juvenile fiction; Flies -- Fiction; Pets -- Fiction; Grandmothers -- Fiction; Humorous stories; Humorous fiction